90=6y-6

Simple and best practice solution for 90=6y-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 90=6y-6 equation:


Simplifying
90 = 6y + -6

Reorder the terms:
90 = -6 + 6y

Solving
90 = -6 + 6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6y' to each side of the equation.
90 + -6y = -6 + 6y + -6y

Combine like terms: 6y + -6y = 0
90 + -6y = -6 + 0
90 + -6y = -6

Add '-90' to each side of the equation.
90 + -90 + -6y = -6 + -90

Combine like terms: 90 + -90 = 0
0 + -6y = -6 + -90
-6y = -6 + -90

Combine like terms: -6 + -90 = -96
-6y = -96

Divide each side by '-6'.
y = 16

Simplifying
y = 16

See similar equations:

| 100=5x+2y+1z | | r+7=8 | | 0.4x+.05(4-x)=.10(-47) | | -3(-3+2x)=-8x+15 | | -10=8n-6+4 | | -13=1+4r-6 | | 7(x+4)-4x=10 | | -6=-4v+v | | 3(5x+2)=2(x+2) | | 4x+43=7x+1 | | 23=7-4m+6m | | 8x+3=4x-9 | | 3x-4y=18 | | 8x+6x=0 | | 3(-x+1)+6x=15 | | 9(t-6)+3t=6(2t+5)-11 | | 14=-7x+5x | | 6m/22(m+n) | | 15X^2Y/-5X^-10Y2 | | -21=3n+(-2) | | 3(8-c)=3c | | 6x^2+6x-4=0 | | -3k-3k=-18 | | 1/6(n-12)=1/4(n+8)-2 | | n/-1.5=-1.2 | | 2-(-10)= | | -18=6(j-5) | | -4=2v-4-2v | | -1(r+8)=0 | | 6x+68=2x+47 | | 6+(-9)+(-8)+7= | | 6a^2-[-5a-(9a^2-3a)]-[8+(19a-8)]= |

Equations solver categories